Proteolysis of histidine kinase VgrS inhibits its autophosphorylation and promotes osmostress resistance in Xanthomonas campestris - Chao-Ying Deng (Nature Portfolio, 2018)
Bacterial histidine kinases (HKs) play key roles in the response to stimuli and are regulated by reversible phosphorylation. Here, the authors show that the activity of a HK in the plant pathogen Xanthomonas campestris is modulated by irreversible, proteolytic modification in response to osmostress.